The role of the World Health Organisation and related funds on maternal and child health in Nigeria - Francis Adah, Oluma; Theophilus Sunday, Gabriel; Mohammed, Kasim; Deák , Máté Sándor; Boruzs, Klára; Bíró, Klára; Bányai, Gábor (Egészségügyi Innovációs Szemle, 2023)
Maternal and child health is extremely important because it serves as the fundamental metric of a successful sciety or nation. This is because every successful conception of a child ensures that there is hope for a better world because each child has the potential to make a positive difference. The demands of mothers’ health must be appropriately met since they have a significant impact on how birth will turn out and, thus, on the continuation of life. The purpose of this study is to provide light on the roles played over time by the World Health Organization, United Nations Children’s Fund, and United Nations Population Fund in influencing maternal and child health in Nigeria. Using a well-established guide on performing systematic reviews and meta-analyses for medical research as well as PRISMA reporting criteria, systematic review was used to effectively search for data related to the steps taken by these multilateral organizations. After carefully evaluating all the publications acquired and ensuring that they met the inclusion and exclusion criteria, respectively, an electronic search was conducted on Google Scholar and PubMed, yielding 49 studies for systematic review. According to the research’s design, the multilateral organizations engaged in the program, the measures taken by those organizations, the country, the target group whether it is for maternal or child health and the state or area in Nigeria where the study was conducted, the data were retrieved. The general quality of the included studies was not astounding this due to the fair rating most of the study received, the availability of the roles in form of intervention or programmes executed by the multilateral organizations involved in this study were very limited upon searching electronically implying that much qualitative and dedicated research on this theme needs to be adequately carried out. This study demonstrates that the three organizations have had a significant impact on Nigeria over the years. However, the World Health Organization has contributed the most to maternal and child health, as evidenced by the targeted programs it has carried out in Nigeria over the years. One significant result of this program was the complete eradication of poliomyelitis in Nigeria.